Correlation and path coefficient analysis in tuberose (Polianthes tuberosa L.) - HARIPRIYA, P KANNAN, G V RAJALINGAM, K (Journal of Spices and Aromatic Crops, 1998)
A study carried out at Tamil N adu, India on the association of metric traits and floral concrete contents of nine ecotypes of tuberose (Polianthes tuberosa) revealed that yield components like length of scape, length of spike, diameter of flower, number of scapes per plant and number of flowers per spike exhibited significant positive association with yield. These components were also positively intercorrelated among themselves. Path coefficient analysis indicated that length of scape, length of spike, number of scapes per plant, number of flowers per spike, vase life, longevity and floral concrete recovery had direct positive effect on flower yield, while diameter of flower had negative direct effect. Length of scape and length of spike were the strongest forces influencing yield.